Technology transfer out of Germany after 1945 - Judt, Matthias 1962- (Studies in the history of science, technology and medicine;, 1996)
The collapse of communism in East Germany has given researchers access to archival sources whose very existence the German Democratic Republic's government denied for many years. The newly available sources have enabled historians to examine long-standing claims both by the Soviets and the Western Allies regarding reparations made by East Germany between 1945 and 1953. East Germany's economic collapse had raised questions about the underlying causes of its considerable economic lag. One explanation favoured by politicians and some historians refers to the different economic burdens which East and West Germany had been forced to bear, and the different levels of intellectual and technological drain which they experienced